PEMANFAATAN BUSINESS INTELLIGENCE UNTUK VISUALISASI DATA DAN PEMETAAN KASUS DATA KELUARGA BERISIKO STUNTING DENGAN MENGGUNAKAN TABLEAU - Alviona Marsya; Darmeli Nasution; Rian Farta Wijaya (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The utilization of Business Intelligence (BI) with Tableau effectively aids in mapping and analyzing cases of families at risk of stunting. Stunting, a condition caused by chronic malnutrition, remains a major health issue in Indonesia, particularly in Langkat Regency, North Sumatra. A quantitative research methodology was applied using the BI framework, encompassing data collection, ETL (Extract, Transform, Load) processes, and interactive visualization through Tableau dashboards. Data from 2022 to 2024, including family risk categories and regional coordinates, were transformed into comprehensive visual representations. The visualization results demonstrate the effectiveness of Tableau in simplifying complex datasets and supporting more targeted interventions. Emphasis is placed on the importance of continuous monitoring and data updates to ensure accurate and timely responses to stunting cases.Â Keyword: Families At Risk Of Stunting; Business Intelligence; Data Visualization; TableauAbstrak: Pemanfaatan Business Intelligence (BI) dengan Tableau mampu membantu memetakan dan menganalisis kasus keluarga berisiko stunting. Stunting, sebagai kondisi kekurangan gizi kronis, menjadi masalah kesehatan utama di Indonesia, khususnya di Kabupaten Langkat, Sumatera Utara. Metodologi penelitian kuantitatif digunakan dengan kerangka kerja BI yang mencakup pengumpulan data, proses ETL (Extract, Transform, Load), serta visualisasi interaktif melalui dashboard Tableau. Data tahun 2022 hingga 2024, meliputi kategori risiko keluarga dan koordinat wilayah, diolah menjadi representasi visual yang komprehensif. Hasil visualisasi memperlihatkan efektivitas Tableau dalam menyederhanakan data kompleks dan mendukung tindakan yang lebih tepat sasaran. Pentingnya pemantauan berkelanjutan dan pembaruan data ditekankan agar respons terhadap kasus stunting dapat dilakukan secara akurat dan tepat waktu.Kata kunci: Keluarga Berisiko Stunting; Business Intelligence; Visualisasi Data; TableauÂ